(3ehOI GdCUMGH aj eSGFd ef GdMSGHs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf hHYO aCbhd GdMSGH edcI ObjbI jZhU UGMHg ai GdML CacGQI Ydi LhGgQ CHcGQg s
(3BNQgG (B:s
(3SJI hJSYhf CNQL efgG GdKdGKI jHb dgG KdGKI hJSYhf hgh GdeWdhH ced GdeQGO efg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B_ (3GdQHGW (B(495 d) s
Keywords: (3GdeLGejYs